1993
DOI: 10.1099/0022-1317-74-1-81
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of African horsesickness virus serotype 4-induced polypeptides in Vero cells and their reactivity in Western immunoblotting

Abstract: The structural and non-structural proteins induced by African horsesickness virus serotype 4 (AHSV-4) in infected Vero cells were analysed by SDS-PAGE. Twenty-two virus-induced polypeptides were detected in infected cells by comparison with the polypeptides of mock-infected cells, of which four major (VP2, VP3, VP5 and VP7) and three minor (VP1, VP4 and VP6) structural proteins and four non-structural proteins (P58, P48, P21 and P20) were shown to be virus-coded, as deduced from electrophoretic and antigenic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…We have observed in purified virus three distinct forms of VP5 with different migration rates in SDS-PAGE (VP5, VP5' and VP5"), which after recovery and re-analysis by SDS-PAGE all comigrate and therefore appear to be of similar M r. It is considered likely that VP5 can adopt different conformational structures which are at least partially dependent on the reducing environment used and which alter its rate of migration during SDS PAGE. Laviada et al (1993) also detected a second protein band in the region of VP5 when purified particles of AHSV-4 were analysed by SDS-PAGE. They confirmed its relatedness to VP5 by its reaction with a VP5-specific monoclonal antibody.…”
Section: Discussionmentioning
confidence: 99%
“…We have observed in purified virus three distinct forms of VP5 with different migration rates in SDS-PAGE (VP5, VP5' and VP5"), which after recovery and re-analysis by SDS-PAGE all comigrate and therefore appear to be of similar M r. It is considered likely that VP5 can adopt different conformational structures which are at least partially dependent on the reducing environment used and which alter its rate of migration during SDS PAGE. Laviada et al (1993) also detected a second protein band in the region of VP5 when purified particles of AHSV-4 were analysed by SDS-PAGE. They confirmed its relatedness to VP5 by its reaction with a VP5-specific monoclonal antibody.…”
Section: Discussionmentioning
confidence: 99%
“…Two related protein products were synthesized from AHSV S10 in in vitro translation studies, and their counterparts identified in AHSV infected cells. These proteins were termed NS3 and NS3A in accordance with BTV nomenclature [37], but they have also been described as NS4 and NS4a [12], and P21 and P20 [20]. Based on AHSV genome coding assignments (R. O'Hara, pers.…”
Section: Introductionmentioning
confidence: 98%
“…proteins are synthesized in infected cells [4,12,20,26]. The gene products of the smallest genome segment of BTV, segment 10 (S10), are the minor nonstructural proteins NS3 and NS3A.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of serum samples from uninfected, experimentally infected and vaccinated horses suggests that the assay offers high sensitivity, specificity and reproducibility (Table ). VP7 was selected as a viral antigen because it is the main target protein for group‐specific diagnosis (OIE, ), while NS3, the second most variable AHSV protein, was selected because it is not expressed in horses vaccinated with inactivated AHSV4 vaccine, allowing DIVA diagnosis (Laviada et al., ). All animals vaccinated with inactivated AHSV4 vaccine in our study were positive for VP7 and negative for NS3 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To avoid these drawbacks, new vaccines, such as killed vaccines, DNA vaccines or recombinant vaccines, have been developed as an alternative to attenuated vaccines (Laviada et al., ; Guthrie et al., ; Alberca et al., ), and this new generation of vaccines enables the development of diagnostic methods that differentiate infected from vaccinated animals (DIVA). One example of these DIVA vaccines is a purified, inactivated AHSV4 vaccine that does not induce antibodies against NS3 (Laviada et al., , ). The use of such vaccines, combined with a reliable DIVA test against AHS that can simultaneously detect antibodies against different AHSV antigens in a single sample, would allow the rapid assessment of whether individual horses have not been infected, have been infected or have been vaccinated.…”
Section: Introductionmentioning
confidence: 99%